2023
DOI: 10.1177/03635465231161372
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between the Joint Space and Outcomes After Hip Arthroscopic Surgery for Femoroacetabular Impingement: Reevaluating the 2-mm Rule

Abstract: Background: A limited joint space (<2 mm) is associated with poorer outcomes and conversion to total hip arthroplasty (THA) after hip arthroscopic surgery. As indications for hip arthroscopic surgery expand, it is important to reevaluate established risk factors among large patient populations. Purpose: To reevaluate the relationship between the radiographic joint space and outcomes after hip arthroscopic surgery and to assess the validity of a joint space of 2 mm as the accepted cutoff for successful hip a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 48 publications
(62 reference statements)
0
5
0
Order By: Relevance
“…Regarding Tönnis classification, our findings validate previous studies correlating higher grades with inferior outcomes at all follow-up time points. 6 , 8 , 12 , 38 , 59 Also using preoperative radiographs, Philippon et al 43 and Ruzbarsky et al 50 reported an association between diminished joint space and higher rates of conversion to THA. The present study similarly identified this association but only in the sensitivity analysis not including Tönnis grade.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding Tönnis classification, our findings validate previous studies correlating higher grades with inferior outcomes at all follow-up time points. 6 , 8 , 12 , 38 , 59 Also using preoperative radiographs, Philippon et al 43 and Ruzbarsky et al 50 reported an association between diminished joint space and higher rates of conversion to THA. The present study similarly identified this association but only in the sensitivity analysis not including Tönnis grade.…”
Section: Discussionmentioning
confidence: 99%
“…Again, this limitation is intrinsic to the study design, and excluding these patients would both inflate survival estimates and preclude substantiation of established risk factors (eg, Tönnis grade ≥2 or severe joint space narrowing). 12 , 38 , 43 , 50 Third, due to the relatively recent practice of routine PROM collection, preoperative PROMs were not available, preventing the analysis of postoperative score changes or clinically meaningful improvements and representing an important consideration for future investigations. However, the primary outcome of this study was conversion to THA; the lack of preoperative PROMs did not diminish our ability to establish associations between patient-specific characteristics and rates of conversion.…”
Section: Discussionmentioning
confidence: 99%
“…This is important as high-resolution 3D sequences for evaluation of cartilage and labrum are commonly acquired in most institutions as part of the routine workup. Volumetric analysis of cartilage thickness yields great potential to improve the moderate prognostic value which has been demonstrated for indirect assessment of cartilage thickness based on evaluation of radiographic joint space narrowing 14,15 .…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, two patients, age 39 and 54 with minimum joint space of 2.1 and 1.2 mm, respectively, at time of surgery converted to THA. Studies have demonstrated joint space, presence of severe chondral defects and age to be important predictors of failure [ 39 , 40 ]. Patients at risk of early failure of hip arthroscopy should be educated on the success rates of both procedures, the expected recoveries, as well as the rehabilitation.…”
Section: Discussionmentioning
confidence: 99%